2008
DOI: 10.2459/jcm.0b013e3282785288
|View full text |Cite
|
Sign up to set email alerts
|

Persistent second-degree atrioventricular block following adenosine infusion for nuclear stress testing

Abstract: The agents used for nuclear stress testing (NST) including adenosine, dobutamine, and dipyridamole, are generally well tolerated and the incidence of serious complications associated with their use in NST is relatively low. Adenosine possesses a potent inhibitory effect on the atrioventricular (AV) node and may induce a transient conduction defect which could result in first-, second-, or third-degree heart block in some patients. The use of the potent AV nodal blocker adenosine for nuclear stress testing in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
0
15
0
3
Order By: Relevance
“…We propose asynchronous pacing in AV block because the risk of asystole under adenosine is high [ 35 ], persistent AV-block after cessation of adenosine infusion has been described [ 36 ]. HR remained constant because AV conduction was impaired and increase in sinus rate due to sympathetic stimulation did not translate into tachycardia making competitive pacing unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…We propose asynchronous pacing in AV block because the risk of asystole under adenosine is high [ 35 ], persistent AV-block after cessation of adenosine infusion has been described [ 36 ]. HR remained constant because AV conduction was impaired and increase in sinus rate due to sympathetic stimulation did not translate into tachycardia making competitive pacing unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…15 Adenosine binds to cardiac A1 receptors, which initiates a cascade through activation of adenyl cyclase, decreasing intracellular cyclic adenosine monophosphate (cAMP), which results in decreased inward calcium conductance. 16 This results in depressed sinoatrial (SA) node activity (negative chronotropic effect), slowed atrioventricular (AV) nodal conduction (negative dromotropic effect), and decreased atrial contractility and ventricular automaticity. 17 The clinical effect is seen 10 to 20 seconds after bolus injection of adenosine, leading to AV nodal blockade, bradycardia, sinus pauses, and cardiac arrest; all of this causes a decrease in cardiac output and mean arterial pressure (MAP).…”
Section: Adenosinementioning
confidence: 99%
“…20,21 Chronic smokers without the presence of severe reactive airway disease do not pose any risk of bronchospasm with adenosine. 33 Another situation in which one needs to be cautious with adenosine use was pointed out by a study by Makaryus et al, 16 which reported development of a persistent AV block in patients with pre-existing right bundle branch block, when large doses of adenosine (47 mg over 5 minutes) were used and required postoperative permanent pacemaker implantation. Adenosine action on the coronary vasculature causes vasodilation, and this results in coronary vascular steal phenomenon in patients with cardiac ischemia.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…In the Adenoscan multicenter trial registry, it was found that 706 out 9,250 patients (7.6 %) undergoing stress testing with adenosine developed transient atrio-ventricular (AV) conduction block [22]. Makaryus et al [23] reported the development of a persistent AV block in patients with pre-existing right bundle branch block after large doses of adenosine (47 mg over 5 min). Therefore, in our opinion anesthesiologists should be cautious about using adenosine in patients with pre-existing conduction defects.…”
Section: Precautionsmentioning
confidence: 99%